Transcriptome Analysis of Oleoresin-Producing Tree Sindora Glabra and Characterization of Sesquiterpene Synthases - Yu, Niu; Yang, Jin-Chang; Yin, Guang-Tian; Li, Rong-Sheng; Zou, Wen-Tao (Frontiers in Plant Science, 2018)
Terpenes serve important physiological and ecological functions in plants. Sindora glabra trees accumulate copious amounts of sesquiterpene-rich oleoresin in the stem. A transcriptome approach was used to determine the unique terpene biosynthesis pathway and to explore the different regulatory mechanisms responsible for the variation of terpene content among individuals. Analysis of de novo-assembled contigs revealed a complete set of genes for terpene biosynthesis. A total of 23,261 differentially expressed unigenes (DEGs) were discovered between high and low oil-yielding plants. DEG enrichment analysis suggested that the terpene biosynthesis process and the plant hormone signal transduction pathway may exert a major role in determining terpene variation in S. glabra. The expression patterns of candidate genes were further verified by quantitative RT-PCR experiments. Key genes involved in the terpene biosynthesis pathway were predominantly expressed in phloem and root tissues. Phylogenetic analysis and subcellular localization implied that S. glabra terpene synthases may evolve from a common ancestor. Furthermore, two sesquiterpene synthase genes, SgSTPS1 and SgSTPS2, were functionally characterized. SgSTPS1 mainly generated β-caryophyllene from farnesyl pyrophosphate. SgSTPS2 is a versatile enzyme that catalyzes the formation of 12 sequiterpenes from farnesyl pyrophosphate and synthesis of three monoterpenes using geranyl pyrophosphate. Together, these results provide large reservoir for elucidating the molecular mechanism of terpene biosynthesis and for exploring the ecological function of sesquiterpenes in S. glabra.